INCIDENCIA DE LA EMPRESA FUNERARIA JARAMILLO EN LA CONDUCTA DE LOS CONSUMIDORES Y SU PODER DE MERCADO EN LA CIUDAD DE LOJA, 2013 - Flores Zapata, Henry Alexander (2015)
In the city of Loja, with regard to the market of products through services, the Funeral Home Jaramillo is a brand leader in the provision of comprehensive products through services, thanks to his experience in more than 44 years, positioning strategies, and have trained professionals at the service of the customer. With the time, the demands of the consumers in the products through services are larger and require the improvement of the same, but in the market new companies have appeared in the field of products through services, thereby generating the competition. Thus, it poses the following item: "The Impact of the funeral company Jaramillo in the consumer behavior and its market power in the city of Loja, 2013 ". The overall objective of the investigation was "Determine the market power of the company products through Funeral services Jaramillo and his impact on the behavior of the consumers of the inhabitants of the city of Loja, year 2013 "; which took the opinion of consumers and prospects for the owners of the 4 most important funerary enterprises of the city of Loja. Taking into account the population of the city of Loja 180 617 inhabitants took a sample of 384 people to be able to analyze the demand and the satisfaction that give the products through services. The methods used were: inductive, analytical and descriptive. Once obtained the results of the surveys and interviews, an analysis has been made of the same, where you can see that the 4 companies, providing products through services according to the needs of the client, through a number of different plans. In addition, it is concluded that the citizenship has more preference for the funeral home Jaramillo, whose services are the most outstanding dynasty rooms, the service of cremation and the cemetery next to open its doors. The Funeral Home Jaramillo has a greater market share with 57.7 % and there is an economic concentration very high of 4120 according to the index Herfindahl-Hisrchman in the market of products through services. In the city of Loja is notes that there is an oligopoly because the market is controlled by very few companies that if they can influence the price of products through services. Keywords: Funeral Jaramillo, market power, Funeral services, Loja.